1999
DOI: 10.1152/jn.1999.82.3.1465
|View full text |Cite
|
Sign up to set email alerts
|

Oscillatory Membrane Potential Activity in the Soma of a Primary Afferent Neuron

Abstract: In the present report, we provide evidence that mesencephalic trigeminal (Mes-V) sensory neurons, a peculiar type of primary afferent cell with its cell body located within the CNS, may operate in different functional modes depending on the degree of their membrane polarization. Using intracellular recording techniques in the slice preparation of the adult rat brain stem, we demonstrate that when these neurons are depolarized, they exhibit sustained, high-frequency, amplitude-modulated membrane potential oscil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
42
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 58 publications
9
42
0
Order By: Relevance
“…In many experiments, 4-AP (Sigma, St. Louis, MO) was added to the superfusion solution at a concentration of 1 mM. This concentration is widely used in vitro, although in slice preparations where capsular diffusion barriers are absent, a lower concentration may be preferred [e.g., 200 M used by Pedroarena et al (1999)]. All cells reported here had a stable resting membrane potential (V r ) more negative than Ϫ45 mV and an overshooting spike on intracellular (somatic) or extracellular axonal stimulation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In many experiments, 4-AP (Sigma, St. Louis, MO) was added to the superfusion solution at a concentration of 1 mM. This concentration is widely used in vitro, although in slice preparations where capsular diffusion barriers are absent, a lower concentration may be preferred [e.g., 200 M used by Pedroarena et al (1999)]. All cells reported here had a stable resting membrane potential (V r ) more negative than Ϫ45 mV and an overshooting spike on intracellular (somatic) or extracellular axonal stimulation.…”
Section: Methodsmentioning
confidence: 99%
“…Bursting may occur when tonic firing activates a prolonged afterhyperpolarization (AHP), which stops the firing until the next burst is triggered. Oscillations reflect rapidly reciprocating transmembrane Na ϩ and K ϩ currents, DAPs reflect rebound from the postspike hyperpolarization, and prolonged AHPs reflect recruitment of a Ca 2ϩ -activated K ϩ current (Amir and Devor, 1997;Amir et al, 1999Amir et al, , 2002aPedroarena et al, 1999;Wu et al, 2001;Xing et al, 2003). Oscillations and DAPs are related, but not identical, phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…For type I SA with a bursting or irregular pattern, it was proposed that an oscillation triggered the first spike of each burst of discharges (Amir et al, 1999(Amir et al, , 2002b. The mechanism for SMPO might be attributable to the interaction between a tetrodotoxin (TTX)-sensitive Na ϩ conductance and a passive voltage-independent K ϩ conductance (Pedroarena et al, 1999;Amir et al, 2002a;Enomoto et al, 2006). However, it is not clear which currents might contribute to the different patterns of SA, or to the oscillation-induced triggering of action potentials.…”
Section: Functional Significance Of Spontaneous Ectopic Generators Inmentioning
confidence: 99%
“…Recently, it was demonstrated that Mes V neurons show conditional burst generation in response to maintained membrane depolarization (Pedroarena et al, 1999;Wu et al, 2001Wu et al, , 2005. Evidence was provided that I NaP amplifies a K ϩ -dependent membrane resonance to initiate subthreshold membrane oscillations.…”
Section: Introductionmentioning
confidence: 99%